A novel metagenomic short-chain dehydrogenase/reductase attenuates Pseudomonas aeruginosa biofilm formation and virulence on Caenorhabditis elegans. - Patrick Bijtenhoorn (Public Library of Science (PLoS), 2011)
In Pseudomonas aeruginosa, the expression of a number of virulence factors, as well as biofilm formation, are controlled by quorum sensing (QS). N-Acylhomoserine lactones (AHLs) are an important class of signaling molecules involved in bacterial QS and in many pathogenic bacteria infection and host colonization are AHL-dependent. The AHL signaling molecules are subject to inactivation mainly by hydrolases (Enzyme Commission class number EC 3) (i.e. N-acyl-homoserine lactonases and N-acyl-homoserine-lactone acylases). Only little is known on quorum quenching mechanisms of oxidoreductases (EC 1). Here we report on the identification and structural characterization of the first NADP-dependent short-chain dehydrogenase/reductase (SDR) involved in inactivation of N-(3-oxo-dodecanoyl)-L-homoserine lactone (3-oxo-C(12)-HSL) and derived from a metagenome library. The corresponding gene was isolated from a soil metagenome and designated bpiB09. Heterologous expression and crystallographic studies established BpiB09 as an NADP-dependent reductase. Although AHLs are probably not the native substrate of this metagenome-derived enzyme, its expression in P. aeruginosa PAO1 resulted in significantly reduced pyocyanin production, decreased motility, poor biofilm formation and absent paralysis of Caenorhabditis elegans. Furthermore, a genome-wide transcriptome study suggested that the level of lasI and rhlI transcription together with 36 well known QS regulated genes was significantly (≥10-fold) affected in P. aeruginosa strains expressing the bpiB09 gene in pBBR1MCS-5. Thus AHL oxidoreductases could be considered as potent tools for the development of quorum quenching strategies.